Hungary : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper analyzes empirically the main determinants of Hungary's inflation rate during 1990-96. Although there exist a number of possible methodologies to analyze this issue, the one proposed in the paper takes explicit account of the time-series properties of the variables that are potential candidates for explaining Hungary's inflation performance. This leads to the specification of a long-term equation, linking consumer prices to a number of macroeconomic variables as well as to proxies for relative price shocks. The paper also examines the external current account and net foreign assets in Hungary.